MATRIX ALGORITHMS OF ENCRYPTIC PROTECTION OF INFORMATION AND EXCHANGE OF ENCRYPTION KEY - Beletsky А.Я.; Beletsky, O.A.; Stecenko Д.А. (Journal of Information Technologies in Education (ITE), 2010)
The algorithms of the exchange of encryption keys between users of computer networks and cryptographic protection of information transmitted over open communications channels. The algorithm is based a modified asymmetric protocol Diffie-Hellman (DH). The essence of the modification amounts to the replacement of large prime numbers algorithm DH guaranteed nonsingular n-complete binary matrices of high order. The methods of synthesis of these matrices. Discussed ways to counter attacks on the encryption algorithm.